Предмет: Алгебра,
автор: Розмари12
(2х+3)^2=(3х-1)^2 срочно
Ответы
Автор ответа:
0
(2x + 3)^2 - (3x - 1)^2 = 0
(2x + 3 - 3x + 1)(2x + 3 + 3x - 1) = 0
( - x + 4)(5x + 2) = 0
- x + 4 = 0
- x = - 4
x = 4
5x + 2 = 0
5x = - 2
x = - 2/5 = - 0.4
(2x + 3 - 3x + 1)(2x + 3 + 3x - 1) = 0
( - x + 4)(5x + 2) = 0
- x + 4 = 0
- x = - 4
x = 4
5x + 2 = 0
5x = - 2
x = - 2/5 = - 0.4
Похожие вопросы
Предмет: Алгебра,
автор: nastyazakieva031
Предмет: Химия,
автор: rmikincuk
Предмет: История,
автор: moonsoulle
Предмет: Литература,
автор: УЧЕНИЧЁКчек